The effect of compensation, work discipline and achievement motivation on employee performance - FITRI REZEKI; Rahmat Hidayat (STIE Binaniaga, 2021)
The business world is now prosecuted to create high employee performance for office development. The office must be able to build and improve performance within its environment. The most common problem is Sukamahi Central Cikarang Office. Which is in the field of serving to the society and goverment is related to the motivation of achieving a decline resulting from bonuses and wages that are less the main factor of discipline in the work decreases. Researchers set the population in this study are employees of Kantor Desa Sukamahi Central Cikarang. The results showed that partial compensation had no effect on the performance of the employees of Sukamahi Central Cikarang Office, this is shown from the results that Work discipline has an effect on the performance of the employees of Kantor Desa Sukamahi Cikarang Pusat as indicated by the results. Achievement also has a positive effect on employee performance and this is shown from the results. From the above statement it can be concluded that partially Work Discipline and Achievement Motivation on Employee Performance influences, While Compensation does not affect performance employe Sukamahi Central Cikarang Office